Trajectories of Mental Health Status Among Police Recruits in Sweden - Emsing, Mikael; Padyab, Mojgan; Ghazinour, Mehdi; Hurtig, Anna-Karin (Frontiers in Psychiatry, 2022)
Background The stressful and complex nature of police work and its adverse effects on mental health are well-documented in police research. The mental health of police students however, has not been given the same attention. To the best of our knowledge, studies on the mental health of Swedish police recruits have not been undertaken since 2010. Objectives The present study aims to examine whether there are differences in the mental health between two cohorts (2009 and 2020) of Swedish police recruits, as well as to compare the mental health of both cohorts with the general population data collected in 2002. Methods Data was collected using the SCL-90-R survey. Data was analyzed using multivariate analysis of variance (MANOVA) and independent sample T-tests. Bi-variate analyses including t-test and chi-square were used to examine differences in sociodemographic variables between the two cohorts. Results A total of 376 police recruits participated in the study. Results indicated no significant differences between the cohorts with regards to the three global indices of the SCL-90-R: Global Severity Index (GSI), Positive Symptom Total (PST), and Positive Symptom Distress Index (PSDI). Recruits with a college degree had lower scores on GSI and PSDI, similar to respondents that where in a relationship vs. singles. A total of 15 (four female) recruits had GSI scores above the Swedish patient mean. Compared with the general population, males and females from the 2009, as well as females from the 2020 cohorts had lower or insignificantly different mean scores on all global indices, with males from the 2020 cohort having a significantly lower PST score. Conclusions While the vast majority of recruits had results that where indicative of a low prevalence and intensity with regards to mental health disorders, some recruits did score above the Swedish patient mean. While mental preparedness is part of the curriculum for Swedish police recruits, interventions targeting the stigmas of poor mental health could be of value. The fact that educational attainment appears to have a positive impact on the mental health of police recruits, could be taken in to consideration when recruiting future police officers.